Children's Play and Learning in Brazil (Springer International Publishing, 2018)
This book presents for the first time in English language an overview of the research done in Brazil in the field of studies of children's play. The volume brings together contributions from researchers of the Working Group Toy, Education and Health, of the Brazilian National Association of Research and Graduate Studies in Psychology (ANPEPP), including empirical studies and literature reviews about indigenous children, riverside communities, urban children in situation of social vulnerability, projects of early childhood education and the ludic possibilities of digital technologies. It aims to show the cultural diversity of Brazil expressed in its children's play, providing valuable resources for international researchers of play interested in intercultural studies. .